THE PURVIEW OF PHYTOTHERAPY IN THE MANAGEMENT OF KIDNEY DISORDERS: A SYSTEMATIC REVIEW ON NIGERIA AND SOUTH AFRICA - Saheed, Sabiu; Hendrik, O’Neill Frans; Omotayo Tom, Ashafa Anofi (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The kidney is tasked with a number of metabolic functions in the body. In its role as a detoxifier and primaryeliminator of xenobiotics, it becomes vulnerable to developing injuries. Currently, over 1 million people in the world are living onrenal replacement therapies (RRTs). The case in sub-Sahara African countries like Nigeria and South Africa is not any better thanthe global trend.Materials and Methods: A systematic review of medicinal plants used in the treatment of kidney disorders was conducted.Information were gathered from published scientific journals, books, reports from national, regional and international institutions,conference proceedings and other high profile intellectual resources. MeSH words like ‘prevalence of kidney disorders in Africa’,‘renal replacement therapy’, ‘nephrotoxins or nephrotoxicants’, ‘nephroprotective plants’, ‘nephroprotective plants in Nigeria orSouth Africa’ and ‘nephroprotective phytocompounds’ were used to retrieve information from online databases (Google, Pubmed,MEDLINE, Science Direct, Scopus and SID).Results: Interestingly, our findings revealed that phytotherapy has emerged and is being employed to protect renal functions anddelay progression of renal pathological conditions into end episodes where the last resort is RRT. In fact, in recent times,Phytotherapists are not only interested in developing relatively safe, more affordable, easily accessible and potent nephroprotectiveformulations but also increasing awareness on the prevalence of the disease and educating the populace on the probable preventivemeasures. More importantly, efforts at scientifically elucidating the pharmacological efficacy of the identified nephroprotectiveplants yet to be validated must be intensified through informed expert opinions. Till date, there is paucity of information on theconcept of nephroprotection in most developing countries where kidney disorder is a major threat. Although, the concept is justemerging in South Africa, evidences have given credence to its application in complementary and alternative system of medicine inNigeria.Conclusion: This review, therefore, reawaken researchers’ consciousness in the continuous search for auspicious nephroprotectiveplants that could potentially be excellent candidates in developing new lead drugs to manage and treat renal disorders.